Ant tending impairs performance of Aenasius bambawalei by manipulating the honeydew composition produced by Phenacoccus solenopsis. (18th May 2015) - Zhou, A. M.; Kuang, B. Q.; Gao, Y. R.; Wang, M.‐Q.
Abstract: Honeydew produced by hemipterans is known as a possible kairomonal resource for parasitoids. The application of artificial honeydew effectively improves the performance of natural enemies. Aenasius bambawalei is a particularly dominant and aggressive endoparasitoid of the invasive mealybug Phenacoccus solenopsis . Our previous study showed that tending by the ghost ant Tapinoma melanocephalum significantly reduced the parasitism of A. bambawalei . We hypothesize that ghost ant tending influences host location of parasitoids by manipulating the composition of the honeydew produced by mealybugs. In this study, we tested whether the honeydew composition differs between treatments with and without ant attendance and whether changes in the honeydew influence the performance of A. bambawalei . Our results show that the sucrose concentration increased significantly in the ant‐attendance treatment but decreased when ant attendance was switched to an ant‐exclusion treatment; the inverse was true for the glucose concentration. Compared with the plastic honeydew treatment (mealybug with ant attendance), parasitoids spent much more time searching, had longer lifespans and showed higher parasitism on filter papers treated with natural honeydew (mealybug without any pre‐treatment) and those treated with convalescent honeydew (mealybug having experienced ant attendance and then switched to ant exclusion). These results support the hypothesis that ant tending influences the performance of parasitoids by manipulating honeydew composition.